Pengukura Suhu dengan Ir MLX90614 dan NoDeMCU dan Membandingkan dengan Ds18B20 untuk pencegahan Covid 19 - Dani sasmoko; Nur Afifah; Iman Saufik (STEKOM PRESS, 2021)
This research was carried out by comparing the DS18B20 sensor and the MLX 90614 sensor to detect the accuracy of detecting human body temperature which is used to detect Covid 19 symptoms. In this experiment, 10 trials were carried out with different human segments detected using the sensor. In the experiment, it was found that the MLX90614 sensor is more suitable to be used for development with an IoT-based system because it does not need to come into contact with the skin of the human body. The MLX90614 sensor will detect the temperature and change it to one Celsius unit then send it to the firebase database which will then be picked up by the android application which is held by the security officer so that the temperature can be known remotely. When the temperature is more than 38.5 Celsius it will turn on the buzzer sound which can be heard from a distance which indicates the temperature is above 38.5 Celsius and on android will also display a danger sign